DESTINATION DEVELOPMENT MODEL FOR FOREIGN SENIOR TOURISTS - I Gusti Bagus Rai Utama; Putu Chris Susanto (Journal of Business on Hospitality and Tourism, 2016)
This study aims to produce a destination development model for foreign senior tourists, involving 400 respondents and 40 tourism professionals as informants. The concept and theory as the basis of confirmation is the totality of tourism product (4A), which consists of attractions, accessibility, amenities, and ancillary services. Senior tourists tend to seek cultural attractions, art performances, festivals, natural attractions, and fair prices such as ones found in traditional markets. For amenities, seniors expect certain amenities such as: places for rest and relaxation, new facilities, places to gain knowledge and experience, places to escape the daily routine, places to meet people and interact, and senior-friendly accommodations. In terms of accessibility, seniors expect the availability of local transportation, tourism infrastructure, senior-friendly airport facilities and services. For ancillary services, seniors expect to get proper guidance and assistance throughout their visit. For local communities, the development of tourism destination specifically geared to attract seniors has a sizeable implication on the availability of employment but is difficult to develop because the facilities and infrastructure involved require significant investment.